Mitigating Youth Unemployment through Pre-service experience Acquisition under Parent-Employer Collaborative arrangements - Kiyita M. Kymabadde (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2022)
The article examines the possibility and challenges of redressing graduate unemployment through parent-employer collaboration that revolves around of remuneration of pre-service em-ployment. The paper used a qualitative research design involving a review of grey literature from published articles and reports on theories and challenges of global, regional and Uganda’s youth unemployment, particularly graduate unemployment and the strategies being applied to mitigate it. Paper findings show the potential for adopting the proposal, given the benefits it is likely to generate for parents, fresh graduates, employers and the government. The proposed arrangement equips fresh graduates with practical working experience which enhanc-es job prospects; employer obtains value added from fresh graduate services at lower cost, and an opportunity to recruit the graduate as a permanent employee; the parent enjoys reduced cost incurred on spending on endless search for jobs by students. Both the government and society benefit through lower social costs due to reduced time graduates spend unemployed as well as greater contribution realized from their work. Findings make significant contribution to knowledge and practice on alleviating graduate unemployment, through parent-employer col-laboration that generates benefits for parents, fresh graduates, employers and the government